Can a referral diagnosis code for duplex ultrasound "predict" carotid artery stenosis? - O. V. Gaisenok; I. V. Samorodskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the detection rate of carotid artery stenosis (CAS) based on the diagnosis code according to the International Classification of Diseases of 10th revision (ICD-10), used in appointment card for carotid duplex ultrasound.Material and methods. To conduct this study, the Duplex-2013 registry database was used, which sequentially included 2548 patients. When referring to carotid duplex ultrasound, all patients indicated the ICD-10 diagnosis code as the main reason for seeking medical help. The study assessed the presence and severity of CAS, the probability of CAS, taking into account age, sex, and referral diagnosis according to ICD-10.Results. According to the results of a univariate analysis, the following referral diagnoses were associated with the identification of CAS by two criteria (stenosis ≥20 and ≥50%): generalized/peripheral atherosclerosis (GPA) — odds ratio (OR), 6,54; 95% confidence interval (CI): 2,71-18,89 (p<0,001) and OR, 11,91; 95% CI: 6,17-22,75 (p<0,001), postinfarction cardiosclerosis — OR, 5,63; 95% CI: 2,62-13,6 (p<0,001) and OR, 3,08; 95% CI: 1,39-6,28 (p=0,004), CAS — OR, 3,26; 95% CI: 2,08-5,27 (p<0,001) and OR, 2,29; 95% CI: 1,25-3,96 (p=0,006) and hypertension, OR, 2,2; 95% CI: 1,87-2,58 (p<0,0001) and OR, 1,45; 95% CI: 1,07-1,97 (p=0,02). Taking into account age and sex, the probability of CAS detection (>20%) is associated with HTN — OR, 1,43; 95% CI: 1,19-1,71 (p<0,001), postinfarction cardiosclerosis — OR, 2,89; 95% CI: 1,20-6,94 (p=0,01) and GPA — OR, 4,52; 95% CI: 1,65-12,35 (p=0,003); CAS >50% — acute myocardial infarction — OR, 8,45; 95% CI: 1,32-53,97 (p=0,02) and GPA — OR, 9,82; 95% CI: 4,81-20,04 (p<0,001).Conclusion. Certain groups of referral diagnoses (ICD-10 codes) are associated with a higher probability of CAS. The obtained data needs to be refined in order to optimize routing and referral for carotid duplex ultrasound.